Comparative Analysis of Phraseological Units with the Zoonym Component "Domestic Animal" in the Mordovian and Finnish Languages - Natalya M. Mosina (Publishing house "Sreda", 2022)
The purpose of the study is to identify common and distinctive features of Mordovian and Finnish phraseological units with the zoonym component «domestic animal» based on a comparative study of the characteristics of the studied phraseological units. The relevance of this study is due to the need for a comprehensive study of phraseological units with a zoonym component in the Mordovian (Erzya, Moksha) and Finnish languages in order to identify common and specific features inherent in these linguistic cultures. The obvious insufficiency of studies of phraseological units of the considered thematic group also explains the study of phraseological units, which have zoonymic components in their composition. The object of the study was the phraseological units of the Mordovian and Finnish languages, in which the zoonym component «domestic animal» was identified. Based on the methods of descriptive, comparative, component analysis, as well as the method of continuous sampling, this article highlights the components of the semantic aspect of phraseological units with zoonym components; the dominant images in phraseological units with the seme-zoonym are revealed, the frequency of their use in two languages is analyzed, and the universal and specific phenomena in the Mordovian and Finnish languages are determined. The main material of the study is presented by phraseological units with a zoocomponent in the Mordovian (Erzya and Moksha) and Finnish languages, identified by continuous sampling from explanatory monolingual, bilingual and phraseological dictionaries, as well as texts of fiction and journalistic literature.